Is Competition in Industry Ruinous - Jones, Eliot (Quarterly Journal of Economics, 1920)
Introduction, 473. — I. Comparison of railroads and industrial enterprises, 476. — A. Statistical analysis, 478. — Ratio of fixed to variable expenses, 480. — Ratio of interest charges to total expenses, 481. — Ratio of capital investment to annual value of products, 484. — B. Some theoretical considerations bearing on the differences between railroads and industrial enterprises, 488. — Importance of fixed plant, 488. — Specialized character of plant, 490. — Operation of law of increasing returns, 491. — Presence of joint cost, 492. — Number of competitors, 493. — Effect of slight reduction in prices, 494. — Danger of spoiling the market, 494. — II. Study of individual industries, 497. — Iron and steel, 498. — Anthracite coal, 502. — Harvesting machine, 503. — Sugar, 505. — Tobacco, 507. — Whisky, 509. — Cordage, 511. — Wall paper, 511. — Malt, 512. — Bicycle, 512. — Tin can, 513. — Corn starch, 514. — Sole leather, 515. — Salt, 516. — Asphalt, 517. — Conclusion, 518.